Duolingo in English education: Evidence-based perspectives on learning outcomes - Fitriani Fitriani (Universitas Pendidikan Indonesia, 2024)
The proliferation of Mobile-Assisted Language Learning (MALL) applications has reshaped the landscape of language education, with platforms like Duolingo making language learning more accessible, engaging, and flexible. This study systematically reviews 20 research articles to evaluate Duolingo’s effectiveness in fostering language proficiency, with a focus on vocabulary acquisition, reading comprehension, speaking, listening, and writing skills. The findings indicate that Duolingo is particularly effective at building foundational vocabulary and supporting beginner-level reading and listening comprehension through gamified and personalized learning features. Duolingo’s gamified elements enhance engagement and promote consistent practice, but the platform’s lack of interactive, real-time communication restricts its ability to develop higher-order language skills. This study underscores the complementary role of digital tools like Duolingo within language curricula, particularly in blended or hybrid learning models, where mobile learning can support vocabulary retention and independent study. Findings from this study contribute to the ongoing discourse on the role of MALL in language acquisition, offering practical insights for educators and policymakers considering digital integration in language programs. Abstrak Proliferasi aplikasi pembelajaran bahasa berbasis perangkat seluler (Mobile-Assisted Language Learning/MALL) telah mengubah lanskap pendidikan bahasa, dengan platform seperti Duolingo yang membuat pembelajaran bahasa menjadi lebih mudah diakses, menarik, dan fleksibel. Studi ini secara sistematis mengulas 20 artikel penelitian untuk mengevaluasi efektivitas Duolingo dalam meningkatkan kemahiran bahasa, terutama pada aspek kosakata, membaca, berbicara, mendengarkan, dan menulis. Temuan menunjukkan bahwa Duolingo sangat efektif dalam membangun kosakata dasar dan mendukung pemahaman membaca dan mendengarkan pada tingkat pemula melalui fitur pembelajaran yang digamifikasi dan dipersonalisasi. Elemen gamifikasi di Duolingo meningkatkan keterlibatan dan mendorong praktik yang konsisten, kurangnya interaksi waktu nyata membatasi pengembangan keterampilan bahasa tingkat lanjut. Studi ini menekankan peran pelengkap alat digital seperti Duolingo dalam kurikulum bahasa, terutama dalam model pembelajaran campuran atau hybrid, di mana pembelajaran seluler dapat mendukung retensi kosakata dan pembelajaran mandiri. Temuan dari studi ini berkontribusi pada wacana berkelanjutan tentang peran MALL dalam perolehan bahasa, serta menawarkan wawasan praktis bagi pendidik dan pembuat kebijakan yang mempertimbangkan integrasi digital dalam program bahasa. Kata Kunci: Duolingo; keterampilan bahasa Inggris; pembelajaran bahasa dengan bantuan ponsel